Antibiotic Residues in Cultured Fish: Implications for Food Safety and Regulatory Concerns - Dragana Ljubojević Pelić; Vladimir Radosavljević; Miloš Pelić; Milica Živkov Baloš; Nikola Puvača; Jurica Jug-Dujaković; Ana Gavrilović (Fishes)
Antibiotics are widely recognized as significant chemical pollutants that enter the environment and ultimately the food chain. They are extensively used in both aquaculture and terrestrial animal breeding. Antibiotic residues in cultured fish pose significant public health risks, including the potential for antimicrobial resistance and adverse health outcomes. This review examines the widespread use of antibiotics in aquaculture, highlighting key challenges such as the lack of reliable data on antibiotic consumption in many regions as well as variability in regulatory enforcement. While strict regulations in European countries help to mitigate risks, the growing, often unregulated use of antibiotics in low- and middle-income countries exacerbates concerns over food safety. This paper provides an in-depth analysis of global regulatory frameworks and the impact of antibiotic residues on public health, and it offers recommendations for improving the monitoring, regulation, and responsible use of antibiotics in aquaculture in order to ensure safer food products from farmed fish. It contributes to a deeper understanding of the global scope of antibiotic misuse in aquaculture and points to an urgent need for more effective management practices.